Validity of the RSA-RANDOM Test for Young Soccer Players - Martin, Victor; Sanchez-Sanchez, Javier; Ramírez-Campillo, Rodrigo; Nakamura, Fábio Yuzo; Gonzalo-Skok, Oliver (International Journal of Sports Medicine, 2018)
The present study aimed to examine the reliability, usefulness, responsiveness, age-related differences and construct validity of a novel decision-making RSA test (RSA-RANDOM test) in young soccer players. Twenty-five young male soccer players performed the RSA-RANDOM test on 2 occasions separated by 5–7 days to assess test-retest reliability and determine a priori usefulness. Furthermore, the same players executed the RSA-RANDOM test 4 times throughout the season to analyse responsiveness. Forty-five players (U–13 to U–17) were evaluated in such test to examine age-related differences. Finally, 9 players were used to determine the construct validity of the test. Reliability scores showed a high intraclass correlation coefficient (ICC=0.88 to 0.90) and low coefficient of variation (CV=1.0–1.2%). The responsiveness of the RSA-RANDOM test was good, as the typical short- (1.2–1.9%), mid- (1.4–2.4%) and long-term (2.3–3.2%) changes in RSA-RANDOM performance were higher than the CV. Age-related differences analysis showed better RSA-RANDOM performance as age increased in young soccer players. Low (r=−0.50) to moderate (r=−0.75) relationships were found between the RSA-RANDOM test variables (RSA best and mean times) with high-intensity and total distance covered, respectively. A novel decision-making RSA test (RSA-RANDOM) has shown to be reliable and valid in young soccer players.
Keywords: adolescents; fatigue; change of direction; endurance; validation.